Asymmetric Ensemble of Asymmetric U-Net Models for Brain Tumor Segmentation With Uncertainty Estimation - Rosas-Gonzalez, Sarahi; Birgui-Sekou, Taibou; Hidane, Moncef; Zemmoura, Ilyess; Tauber, Clovis (Frontiers in Neurology, 2021)
Accurate brain tumor segmentation is crucial for clinical assessment, follow-up and subsequent treatment of gliomas. While Convolutional Neural Networks (CNN) have become state of the art in this task, most proposed models either use 2D architectures ignoring 3D contextual information or 3D models requiring large memory capacity and extensive learning databases. In this study, an ensemble of two kinds of U-Net-like models based on both 3D and 2.5D convolutions is proposed to segment multimodal Magnetic Resonance Images (MRI). The 3D model uses concatenated data in a modified U-Net architecture. In contrast, the 2.5D model is based on a multi-input strategy to extract low-level features from each modality independently and on a new 2.5D Multi-View-Inception block that aims to merge features from different views of a 3D image aggregating multi-scale features. The Asymmetric Ensemble of Asymmetric U-Net (AE AU-Net) based on both is designed to find a balance between increasing multi-scale and 3D contextual information extraction and keeping memory consumption low. Experiments on 2019 dataset show that our model improves enhancing tumor sub-region segmentation. Overall, performance is comparable with state-of-the-art results, albeit with less learning data or memory requirements. In addition, we provide voxel-wise and structure-wise uncertainties of the segmentation results, and we have established qualitative and quantitative relationships between uncertainty and prediction errors. Dice Similarity Coefficient for the whole tumor, tumor core and tumor enhancing regions on BraTS 2019 validation dataset were 0.902, 0.815 and 0.773. We also applied our method in BraTS 2018 with corresponding Dice score values of 0.908, 0.838 and 0.800.